Unexpected loss of stereoselectivity in glycosylation reactions during the synthesis of chondroitin sulfate oligosaccharides - Mena-Barragán, Teresa; de Paz, José L.; Nieto, Pedro M. (Beilstein Journal of Organic Chemistry, 2019)
Here, we present an exploratory study on the fluorous-assisted synthesis of chondroitin sulfate (CS) oligosaccharides. Following this approach, a CS tetrasaccharide was prepared. However, in contrast to our previous results, a significant loss of β-selectivity was observed in [2 + 2] glycosylations involving N-trifluoroacetyl-protected D-galactosamine donors and D-glucuronic acid (GlcA) acceptors. These results, together with those obtained from experiments employing model monosaccharide building blocks, highlight the impact of the glycosyl acceptor structure on the stereoselectivity of glycosylation reactions. Our study provides useful data about the substitution pattern of GlcA units for the efficient synthesis of CS oligomers.
Keywords: carbohydrate chemistry; chondroitin sulfate; glycosylation; oligosaccharide synthesis; stereoselectivity